Synthesis and characterization of nanocomposites of graphene oxide for the removal of fluoride and lead (II) from water - Mohan, Sweta (My University, 2017)
1 Synthesis and characterization of nanocomposites of graphene oxide for the removal of fluoride and lead (II) from water for the Award of Degree Doctor of Philosophy By Sweta Mohan (Enrollment No. 12611EN007) DEPARTMENT OF CHEMISTRY INDIAN INSTITUTE OF TECHNOLOGY (BANARAS HINDU UNIVERSITY) VARANASI – 221005 (Prof. Syed Hadi Hasan) 2 ABSTRACT The present thesis comprises the studies on the remediation of fluoride and lead ions from the water which was undertaken by the author for her Ph.D work. The thesis has been divided into as many as six chapters. Chapter I includes the general introduction which is based on the statement of the problem and the summary of the work which has been reported in this area in past few decades. This chapter is focussed on environmental pollution in general and water pollution in particular. Water is the utmost vital and essential component on the earth for the survival of all flora and fauna. In past few decades, the quality of water resources continuously degraded because of rapid population growth, fast industrialization, domestic, and agricultural activities, and other geological as well as natural environmental changes. Due to these activities, the water gets contaminated by different types of organic, inorganic, and biological pollutant species. It has been observed from the information collected in this chapter that water pollution has became the major concern in the presents scenario. Water contamination by fluoride (F-) and lead (Pb2+) considered as major concern now a days because pollutant causes severe toxicity which induce lethal and carcinogenic effects. Although fluoride is necessary for bone formation and prevents tooth decay when its concentration is present within the permissible limits. But the excess amount of fluoride causes the detrimental effect on human health leading to dental and skeletal fluorosis, brittle bones, osteoporosis, and arthritis. In addition to these deleterious effects, it can also induce cancer, immunological and birth defects. Water get polluted from fluoride by weathering of fluoride-containing minerals such as fluorite, apatite, rock phosphate and topaz. The discharges from the industries such as semiconductor manufacturing, electroplating, coal, ceramic production aluminum smelter also pollute the water with high concentration of fluoride where the fluorochemicals are being used as main ingredients. The another toxic metal ions 3 which is taken into account in this thesis is the lead which is one of most harmful heavy metal and commonly present in the air, water as well as in the soil . Lead is non-biodegradable and have the ability to accumulate in the living systems because of its ability to mimick the various metals such as calcium, iron, and zinc which participate in various biological functions that make it lethal for living being. Due to these characteristics, it produces various reproductive, genotoxic, and neurological defects as well as also induces carcinogenicity in the human body. Thus, due to deleterious effects of fluoride and lead, these ions proved to be dangerous for flora and fauna of the earth. In the past few years, various techniques have been used such as coagulation, adsorption, membrane filtration, bio-sorption, ion exchange, and precipitation for the removal of fluoride and lead. Among them, the adsorption is considered as one of the most effective and economical method for the water treatment. Previously, many conventional adsorbents have been used i.e. activated carbon, activated alumina, clay, and zeolites which show very low adsorption ability for the removal of these pollutant ions. In the past few years, the nanotechnology has emerges as the new field in this area which involves the synthesis and application of nanomaterials. The nanomaterial has gained the attention of scientists from all the fields because they show unique physical and chemical properties. In context to this the various nanomaterials have been applied for the removal of fluoride and lead. Among carbon nanomaterials, the graphene and its derivative have received more attention as an adsorbent. Graphene and its derivatives showed various superior properties such as extraordinary high surface area, high mechanical strength, strong thermal and chemical stability. Graphene oxide (GO) is an derivative of graphene which exhibit various oxygen 4 functional groups on its surface which can interact with the pollutant ions along with unique properties of graphene thus it would be a excellent adsorbent for water treatment. The term nanocomposite can be defined as the combination of two materials, a filler, and a matrix, to obtain a material with superior properties which is called as composite. In this work two nanocomposite of GO was synthesized which are GO/ZrO2 and GO/MgO. The ZrO2 and MgO showed specific binding ability toward fluoride and lead respectively in turn GO provide high exposed surface area for pollutant ions interaction. Chapter II deals with the materials used and experimental procedures utilized for the proposed work. This chapter also included the detailed characterization techniques which have been utilized for the characterization of synthesized nanocomposites. The detailed experimental process used in batch as well as in fixed bed continuous operations are also given in this chapter. Finally, various mathematical models related to the kinetic, thermodynamic and isotherm studies of this adsorption system were also discussed in this chapter. Chapter III deals with the synthesis of the rGO/ZrO2 nanocomposite which was utilized for the adsorptive remediation of the fluoride from water in batch mode. The nanocomposite of rGO/ZrO2 was prepared by simple one step hydrothermal method by using GO and ZrOCl2.8H2O as the starting materials. Various characterization techniques were implemented to characterized the prepared nanocomposite such as FTIR, XRD, SEM, EDX, Raman, BET, and XPS analysis. The effect of different process parameter on the uptake capacity of fluoride was thoroughly investigated. The batch adsorption experiments results showed that the maximum absorption capacity of rGO/ZrO2 for fluoride was 46 mg/g at 30°C, pH 7, rGO/ZrO2 dose 0.5 g/L and at an initial fluoride concentration of 25 mg/L. The equilibrium time for the adsorption was 50 min. 5 The Langmuir, Freundlich and Dubinin-Radushkevich (D-R) adsorption isotherm models were applied to the equilibrium data at different temperatures viz. 20°C, 30°C, 40°C. The results showed that the Langmuir isotherm model was fitted well to the equilibrium data as compared to Freundlich isotherm model. The applicability of Langmuir isotherm model indicated that the adsorption process was monolayer and occurred on homogenous active sites. The value of n (intensity of adsorption) determined from the Freundlich isotherm was found to be in between 1 and 10 which also represented the favorable adsorption at all the investigated temperatures. The values of E kJ/mol which were determined from the D-R isotherm model lies in the range of chemisorption thus the adsorption of fluoride onto the rGO/ZrO2 was chemical in nature. The thermodynamic parameters (ΔG0, ΔH0, ΔS0) were calculated from the slopes and intercepts of Van’t Hoff plots. The ΔH0 value was observed to be positive which again advocated that the adsorption process was endothermic in nature. The negative values of ΔG0 indicated that the adsorption process was spontaneous thus, it was concluded that the adsorption of fluoride by rGO/ZrO2 was feasible at all studies temperature. The kinetics of the adsorption was studied with the help of various models, and the results showed that the pseudo-second order kinetic model better elucidated the adsorption of fluoride for this system with the significantly high value of R2 than that of pseudo-first order kinetic equation. Therefore, it support fast adsorption as the rate of the adsorption which would be directly proportional to the binding site available on the surface of the adsorbent. Furthermore, the external mass transfer studies was performed with the help of Mckay et al. model by which the coefficient of mass transfer was determined which was found to be in the order of 10-3 cm-1 which supported the fast kinetics of fluoride adsorption. In addition, the Weber-Morris and Richenberg model were also applied to this adsorption system which supports the occurrence of 6 film diffusion followed by intraparticle diffusion during the adsorption process. The mechanism of fluoride adsorption involved hydrogen bonding, electrostatic interaction along with OH- exchange process. In order to confirm the adsorption of fluoride the rGO/ZrO2 nanocomposite before and after adsorption was analyzed by EDX and XPS technique. XPS spectra of Zr indicated that Zr ions play a major role in the adsorption process. Chapter IV is devoted to testing the practical applicability of the prepared rGO/ZrO2 nanocomposite for the adsorptive remediation of fluoride in the continuous up-flow fixed-bed column system. The experiment was carried at laboratory scale with the borosilicate column (height: 30 cm and internal diameter :1 cm) which will be helpful in future for the fabrication of treatment plant for the fluoride removal from water. The performance of fixed bed column is evaluated in terms of the breakthrough curves. The influence of different column parameters viz. bed height, initial fluoride concentration and flow rate on the adsorption performance of the rGO/ZrO2 were also investigated. The results of the parametric evaluation showed that the uptake of fluoride increased with the increase in bed height from 2.5 to 7.5 cm and fluoride concentration from 10 to 25 mg/L. Whereas, the uptake of fluoride decreased with the increase in flow rate of the influent from 1.66 to 4.98 mL/min. The maximum uptake of fluoride was found to be 45.7 mg/g at the flow rate 1.66 mL/min, bed height 7.5 cm and 25 mg/L of fluoride concentration. Different kinetic models i.e. BDST, Thomas and Yoon-Nelson models were also applied to the equilibrium data to predict the behavior of breakthrough curves. The Bed Depth Service Time (BDST) model was utilized to established the relationship between service time and bed depth. In this investigation, the model was applied to different flow rate i.e. 1.66 mL/min and 3.32 mL/min at the fluoride concentration of 25 mg/L. The value of ka increased from 0.00017 to 0.00019 L/mg/min with increase in flow rate from 1.66 to 3.32 mL/min 7 respectively. It was also observed that the values of adsorption capacity decreased from 71550 to 69903 mg/g with the increase in flow rate. The critical bed depth was also increased from the 0.56 to 1.12 cm as the flow rate increased from 1.66 to 3.32 mL/min. Moreover, the BDST model was utilized for the successful prediction of the parameters of the new column at the flow rate of 3.32 mL/min with the known flow rate of 1.66 mL/min. Furthermore, the regeneration studies of the column were conducted with the 10% NaOH solution successfully with a slight decrease in column capacity up to three adsorption-desorption cycles. Life factor calculation revealed that the nanoadsorbent bed would be capable of avoiding the breakthrough at time t = 0 up to 15.11 cycles for the removal of fluoride. Chapter V deals with the synthesis of GO/MgO nanocomposite and its application in lead removal from water by batch system. The nanocomposite was synthesized by simple precipitation method which involves the GO and Mg(NO3)2.6H2O as precursor. The prepared adsorbent was characterized with FTIR, XRD, SEM, EDX, Raman, BET, and XPS analysis. The effect of pH, contact time, initial lead concentration and temperature on the adsorption of lead was also investigated. The result showed that the maximum adsorption capacity of the GO/MgO nanocomposite for the lead was 190 mg/g at 30°C, pH 6.5, GO/MgO dose 0.4 g/L and at initial lead concentration of 80 mg/L. The adsorption process achieved equilibrium within 30 min. Different isotherm models were utilized to explore the adsorption process at three different temperatures i.e. 20, 30, and 40°C. Langmuir isotherm model fitted well to the experimental data which confirmed the monolayer adsorption at energetically equivalent binding sites of the adsorbent. The Freundlich isotherm model gives the value of n (intensity of adsorption) which was lies in between 1 to 10 thus, also validate the favorability of this adsorption process at all the mentioned temperatures. The values of E kJ/mol (mean adsorption energy) determined from the 8 D-R isotherm model observed to be in the range of chemisorption. Therefore, this adsorption process involved chemical adsorption process. Thermodynamic studies gives the value of ΔG0 which was found to be negative whereas, ΔH0 values was observed to be positive. Therefore, the adsorption of lead occurred spontaneously and was endothermic in nature. The kinetic studies showed that the pseudo-second order kinetic model better described this system indicated by its high R2 values in comparison of pseudo-first order kinetic equation. In addition, the external mass transfer studies was performed with the help of McKay et al. model by which the coefficient of mass transfer (βt) was determined. The values of βt was found in the order of 10-3 which supported the fast kinetics of lead adsorption. Furthermore, the Weber-Morris model, and Richenberg model were also applied to the experimental data, and the findings indicated that the film diffusion along with intraparticle diffusion both taken part in the adsorption process. The mechanism of lead adsorption involved the electrostatic interaction as well as ion exchange process. The adsorption of lead was confirmed by analyzing the GO/MgO before and after the adsorption by EDX and XPS analysis. Chapter VI is aimed to focussed on the practical applicability and efficacy of GO/MgO nanocomposite for the removal of the lead by the continuous up-flow fixed-bed column system. The influence of different column parameters viz. initial lead concentration, bed height, and flow rate on the uptake capacity of the GO/MgO was also investigated. The evaluation of different parameters revealed that the absorption capacity was significantly affected by the change in these parameters. The results indicated that the uptake capacity was increased with the increase in bed height from 2.5 to 7.5 cm and increase of lead concentration from 40-80 mg/L. On the other hand, it decreased with the increase in flow rate of the influent from 1.66 to 4.98 mL/min. The maximum adsorption of lead achieved at the bed height of 7.5 cm, lead concentration of 80 mg/L 9 and flow rate of 1.66 mL/min. The BDST model well describe this adsorption system and predict the linear relationship between service time and bed depth. This model was applied at different flow rate viz. 1.66 and 3.32 mL/min and at 80 mg/L of lead concentration. The ka values calculated from BDST plots increased from 0.00025 to 0.00028 with an increase in flow from 1.66 and 332 mL/min respectively. The column capacity showed the decreasing trend from 158112 to 157680 mg/g as the flow rate increased from 1.66 to 3.32 mL/min. The critical bed depth increased from 0.56 to 1.12 cm with increase in flow rate from 1.66 to 3.32 mL/min. Furthermore, the BDST model was also utilized to predict the column parameter of the new column at the flow rate of 3.32 mL/min with the sample flow rate of 1.66 mL/min. The desorption of lead by GO/MgO was performed with 0.1 M HCl solution, and the adsorbent was observed to retain its high adsorption capacity up to three cycles. Life factor calculation indicated that adsorbent bed would have sufficient capacity to avoid breakthrough at time t = 0 up to 6.7 cycles and the bed would be completely exhausted after 17.3 cycles. Thus, it can be concluded that this thesis presented a complete study for the efficient, eco-friendly and economical method that can be successfully utilized for the adsorptive remediation of fluoride and lead from water. Overall, in the last a summary of the work is given which contain the conclusion and major findings of each chapter. The prepared nanocomposites i.e. rGO/ZrO2 and GO/MgO proved to be excellent adsorbent for the removal fluoride and lead respectively. Two methods were adopted for the remediation purpose i.e. batch method and column method. It was found that the column studies are helpful for the fabrication treatment plants whereas, batch method is helpful for optimizing the conditions at which maximum adsorption achieved.
Keywords: Graphene oxide; Removal of fluoride; Lead (II) from water